Families of Halo-like invariant tori around L2 in the Earth-Moon Bicircular Problem - Rosales, José J.; Jorba, Ángel; Jorba-Cuscó, Marc (Celestial mechanics and dynamical astronomy, 2021)
The Bicircular Problem (BCP) is a periodic time dependent perturbation of the Earth-Moon Restricted Three-Body Problem that includes the direct gravitational effect of the Sun. In this paper we use the BCP to study the existence of Halo-like orbits around L2 in the Earth-Moon system taking into account the perturbation of the Sun. By means of computing families of 2D invariant tori, we show that there are at least two different families of Halo-like quasi-periodic orbits around L2.
Keywords: quasi-periodic halo orbits; stability of invariant curves; translunar point; Scopus; WOS(2)